Elimination of Senescent Cells by Senolytics Facilitates Bony Endplate Microvessel Formation and Mitigates Disc Degeneration in Aged Mice - Chen, Bolin; Zhu, Runjiu; Hu, Hao; Zhan, Mingbin; Wang, Tingxuan; Huang, Fangli; Wei, Fuxin; Chai, Yu; Ling, Zemin; Zou, Xuenong (Frontiers in Cell and Developmental Biology, 2022)
Senolytics are a class of drugs that selectively eliminate senescent cells and ameliorate senescense-associated disease. Studies have demonstrated the accumulation of senescent disc cells and the production of senescence-associated secretory phenotype decrease the number of functional cells in degenerative tissue. It has been determined that clearance of senescent cell by senolytics rejuvenates various cell types in several human organs, including the largest avascular structure, intervertebral disc. The microvasculature in the marrow space of bony endplate (BEP) are the structural foundation of nutrient exchange in the intervertebral disc, but to date, the anti‑senescence effects of senolytics on senescent vascular endothelial cells in the endplate subchondral vasculature remains unclear. In this study, the relationships between endothelial cellular senescence in the marrow space of the bony endplate and intervertebral disc degeneration were investigated using the aged mice model. Immunofluorescence staining was used to evaluate the protein expression of p16, p21 and EMCN in vascular endothelial cells. Senescence‑associated β‑galactosidase staining was used to investigate the senescence of vascular endothelial cells. Meanwhile, the effects of senolytics on cellular senescence of human umbilical vein endothelial cells (HUVECs) were investigated using a cell culture model. Preliminary results showed that senolytics alleviate endothelial cellular senescence in the marrow space of bony endplate as evidenced by reduced senescence-associated secretory phenotype. In the aged mice model, we found decreased height of IVD accompanied by vertebral bone mass loss and obvious changes to the endplate subchondral vasculature, which may lead to the decrease in nutrition transport into intervertebral disc. These findings may provide evidence that senolytics can eliminate the senescent cells and facilitate microvascular formation in the marrow space of the bony endplate. Targeting senescent cellular clearance mechanism to increase nutrient supply to the avascular disc suggests a potential treatment value of senolytics for intervertebral disc degenerative diseases.